2014
DOI: 10.1186/s12917-014-0188-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the cellular proteins of A549 infected with Hepatitis E virus by proteomics analysis

Abstract: BackgroundOur understanding of Hepatitis E virus (HEV) has changed enormously over the past 30 years, from a waterborne infection causing outbreaks of acute hepatitis in developing countries to an infection of global distribution causing a range of hepatic and extra-hepatic illness. However, the key proteins playing important parts in the virus infection were still unknown. Understanding the changes of cellular proteins in these cells exposed to HEV is helpful for elucidating molecular mechanisms associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…These results are consistent with the observations of this study, and previous studies demonstrated that the Mongolian gerbil represent a promising model for the studies on HEV infection and pathogenesis ( Doceul et al, 2016 ). In vitro , HEV cultivation was performed using PLC/PRF/5 and A549 using fecal suspension infected with HEV ( Tanaka et al, 2007 , 2009 ; Takahashi et al, 2010 ; Shen et al, 2014 ), and structural changes to the cells were investigated by TEM, showing that the lysosome numbers increased, indicating apoptosis, and cell membrane was damaged ( Shen et al, 2014 ), which was also consistent with our research.…”
Section: Discussionsupporting
confidence: 86%
“…These results are consistent with the observations of this study, and previous studies demonstrated that the Mongolian gerbil represent a promising model for the studies on HEV infection and pathogenesis ( Doceul et al, 2016 ). In vitro , HEV cultivation was performed using PLC/PRF/5 and A549 using fecal suspension infected with HEV ( Tanaka et al, 2007 , 2009 ; Takahashi et al, 2010 ; Shen et al, 2014 ), and structural changes to the cells were investigated by TEM, showing that the lysosome numbers increased, indicating apoptosis, and cell membrane was damaged ( Shen et al, 2014 ), which was also consistent with our research.…”
Section: Discussionsupporting
confidence: 86%
“…A quantitative proteomics study by Rogée et al (2015) evaluating the alteration of host factors during HEV infection in swine revealed an upregulation of HNRNPK in infected livers (Rogée et al, 2015). In another study of modulation of host factors during HEV infection in A549 cells, a significant increase in the expression of HNRNPH was observed in response to virus infection (Shen et al, 2014). Our study is consistent with these findings as it underlines a putative role of hnRNP proteins in modulating HEV RNA transcription by binding at the promoter site and HEV polymerase.…”
Section: Resultsmentioning
confidence: 99%
“…Differential protein profiles of expression that occurred during HEV infection have been reported for g-1, g-3, and g-4 viruses ( 24 26 ). Comparison of the H HEV data set with the g-1, g-3, and g-4 virus data sets revealed that 10/18 (g-1), 7/55 (g − 3), and 2/26 (g − 4) differentially expressed proteins also interact with a viral protein, which might account for their differential expression results ( Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Yellow denotes the target of eIF2AK4. A Web-based tool, Venny 2.1.0 ( http://bioinfogp.cnb.csic.es/tools/venny/index.html ), was used to generate the Venn diagram for comparing the Y2H data set (this study) with the profiles of differentially expressed proteins identified in HEV-infected human, pigs, and A549 cells ( 24 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation